Managing Food Waste: A Thematic Study on Restaurants of Dhaka city - Jahan, Nusrat; Khanum, Shahinor (Bangladesh Journal of MIS, 2025)
Food waste represents a significant challenge within Bangladesh’s food and hospitality industry and globally. Effective prevention strategies and technological management approaches are essential to maintaining food quality and enhancing the economic performance of the hospitality sector. The research aims to identify the most effective prevention and technological management practices. The research used 12 semi-structured interviews and thematic analysis, relying on deductive techniques to generate thematic content. The findings reveal several causes and stages contributing to food waste, with the highest levels observed during preparation and cleaning, as well as from leftover food on guests’ plates. Recovery strategies and technological interventions, such as freezing and cooling systems, vacuum machines, intelligent packaging solutions, and other management tools, were identified as effective in mitigating food waste. Future research in food waste management will be necessary to identify and collect data and to develop operational recommendations, advancing sustainability and operational efficiency in the hospitality sector.
Keywords: Food Waste; Hospitality Industry; Restaurants; Waste Management